The correlation between knowledge and practice of exercise regimens among UP College of Nursing students
This study aims to correlate knowledge and practice of exercise among regular UPCN students enrolled in the second semester of AY. 2011-2012. A 27-item questionnaire was formulated to measure the degree of both components. Sums for each were correlated using Pearson analysis. It was found out that there is no correlation between knowledge and practice among the respondents of the study. This concludes that there is no relationship between knowledge and practice of exercise for UPCN students. There was no knowledge and practice correlation, but there was a noted correlation among the second year students. Further studies must look into such factors that may motivate exercise practice among student nurses.